Initiation of opiate addiction in a Canadian prison: a case report - Wood, Evan (BioMed Central, 2006)
BACKGROUND: In North America, the harms of illicit drug use have been responded to primarily through law enforcement interventions. This strategy has resulted in record populations of addicted individuals being incarcerated in both Canada and the United States. The incarceration of non-violent drug offenders has become increasingly controversial as studies demonstrate the harms, including elevated HIV risk behavior, of incarcerating injection drug users. Other harms, such as the initiation of illicit drug use by prison inmates who previously did not use drugs, have been less commonly described. CASE PRESENTATION: We report on the case of an individual who initiated non-injection opiate use in a Canadian prison and developed an addiction to the drug. Upon release into the community, the individual continued using opiates and sought treatment at a clinic. The patient feared that he might initiate injection use of opiates if his cravings could not be controlled. The patient was placed on methadone maintenance therapy. CONCLUSION: While anecdotal reports indicate that initiation in prison of the use of addictive illicit substances is frequent, documentation through clinical experience is rare, and the public health implications of this behavior have not been given sufficient attention in the literature. Strategies of incarcerating non-violent drug offenders and attempting to keep illicit drugs out of prisons have not reduced the harms and costs of illicit drug use. Effective, practical alternatives are urgently needed; expanded community diversion programs for non-violent drug offenders deserve particular attention.